Comparative analysis of trust and security - Hussain, Farookh Khadeer; Chang, Elizabeth; Dillon, Tharam S. (IEEE Computer Society, 2006)
In the literature, there is a lot of confusion regarding the relationship between the 'trust' and 'security'. Most of the times, these terms are regarded as being synonymous with each other. The existing literature does not draw a clear line how and when the terms of 'trust' and 'security' are synonymous and when they are not synonymous. In this paper we address this issue and discuss when the distinct terms of 'trust' and 'security' can be regarded as being synonymous with each other and when they could be regarded as not being synonymous with each other.